(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
This article demonstrates the parts and relationships oforganizational culture and organizational structure in directing worker conductto key goals, utilizing information processing view, organizational culture andstructure immediate the conduct of workers through the diminishment of lack ofdetermination and dubiousness.